Optimising urinary catecholamine metabolite diagnostics for neuroblastoma - Matser, Yvette A H; Verly, Iedan R N; van der Ham, Maria; de Sain-van der Velden, Monique G M; Verhoeven-Duif, Nanda M; Ash, Shifra; Cangemi, Giuliana; Barco, Sebastiano; Popovic, Maja Beck; van Kuilenburg, André B P; Tytgat, Godelieve A M; SIOPEN Catecholamine Working Group (Pediatric blood & cancer, 2023)
INTRODUCTION: The analysis of urinary catecholamine metabolites is a cornerstone of neuroblastoma diagnostics. Currently, there is no consensus regarding the sampling method, and variable combinations of catecholamine metabolites are being used. We investigated if spot urine samples can be reliably used for analysis of a panel of catecholamine metabolites for the diagnosis of neuroblastoma. METHODS: Twenty-four-hour urine or spot urine samples were collected from patients with and without neuroblastoma at diagnosis. Homovanillic acid (HVA), vanillylmandelic acid (VMA), dopamine, 3-methoxytyramine, norepinephrine, normetanephrine, epinephrine and metanephrine were measured by high-performance liquid chromatography coupled with fluorescence detection (HPLC-FD) and/or ultra-performance liquid chromatography coupled with electrospray tandem mass spectrometry (UPLC-MS/MS). RESULTS: Catecholamine metabolite levels were measured in urine samples of 400 neuroblastoma patients (24-hour urine, n = 234; spot urine, n = 166) and 571 controls (all spot urine). Excretion levels of catecholamine metabolites and the diagnostic sensitivity for each metabolite were similar in 24-hour urine and spot urine samples (p > .08 and >.27 for all metabolites). The area under the receiver-operating-characteristic curve (AUC) of the panel containing all eight catecholamine metabolites was significantly higher compared to that of only HVA and VMA (AUC = 0.952 vs. 0.920, p = .02). No differences were observed in metabolite levels between the two analysis methods. CONCLUSION: Catecholamine metabolites in spot urine and 24-hour urine resulted in similar diagnostic sensitivities. The Catecholamine Working Group recommends the implementation of spot urine as standard of care. The panel of eight catecholamine metabolites has superior diagnostic accuracy over VMA and HVA.
Keywords: tandem mass spectrometry; metanephrines; Vanilmandelic Acid; urine collection; Homovanillic Acid; Neuroblastoma; kyselina homovanilová; neuroblastoma; Humans; diagnostic sensitivity; Tandem Mass Spectrometry; Metanephrine; chromatografie kapalinová; catecholamine metabolites; tandemová hmotnostní spektrometrie; Chromatography, Liquid; neuroblastom; metanefrin; kyselina vanilmandlová; lidé